Association of HLA class I type with prevalence and outcome of patients with acute myeloid leukemia and mutated nucleophosmin - Kuželová, Kateřina; Brodská, Barbora; Schetelig, Johannes; Röllig, Christoph; Ráčil, Zdeněk; Walz, Juliane Stickel; Helbig, Grzegorz; Fuchs, Ota; Vraná, Milena; Pecherková, Pavla; Šálek, Cyril; Mayer, Jiří (PloS one, 2018)
Acute myeloid leukemia with mutated nucleophosmin (NPMc+ AML) forms a distinct AML subgroup with better prognosis which can potentially be associated with immune response against the mutated nucleophosmin (NPM). As the T-cell-mediated immunity involves antigen presentation on HLA class I molecules, we hypothesized that individuals with suitable HLA type could be less prone to develop NPMc+ AML. We compared HLA class I distribution in NPMc+ AML patient cohort (398 patients from 5 centers) with the HLA allele frequencies of the healthy population and found HLA-A*02, B*07, B*40 and C*07 underrepresented in the NPMc+ AML group. Presence of B*07 or C*07:01 antigen was associated with better survival in patients without concomitant FLT3 internal tandem duplication. Candidate NPM-derived immunopeptides were found for B*40 and B*07 using prediction software tools. Our findings suggest that a T-cell-mediated immune response could actually explain better prognosis of NPMc+ patients and provide a rationale for attempts to explore the importance of immunosuppressive mechanisms in this AML subgroup.
Keywords: nádorové proteiny; Disease-Free Survival; Male; Survival Rate; Adult; prevalence; Histocompatibility Antigens Class I; akutní myeloidní leukemie; Aged; dospělí; jaderné proteiny; mužské pohlaví; senioři; MHC antigeny I. třídy; T-lymfocyty; Nucleophosmin; lidé; buněčná imunita; Leukemia, Myeloid, Acute; ženské pohlaví; Humans; Prevalence; Immunity, Cellular; Neoplasm Proteins; T-Lymphocytes; Female; nukleofosmin; lidé středního věku; Nuclear Proteins; přežití bez známek nemoci; míra přežití; Middle Aged